SELF CONFIDENCE DAN HASIL BELAJAR SISWA MELALUI PENDEKATAN PROBLEM SOLVING DI SMAN 1 BONTI - Saparani, Abang Edi; Yani T, Ahmad; Riyanti, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis reseach aimed to know the correlation between self-confidence with learning outcomes after given problem solving approach on linear program class XI SMAN 1 Bonti. The method of this research is pre-experimental and research design one-shot case study. The sample of this research are 28 students. Based on the research findings, it can be concluded that (1) Learning outcomes of students after given problem solving approach on linear program is 73.21 included in medium category. (2) Self confidence of students after given problem solving approach on linear program is 69.05% included in high category. (3) Based on results of test statistics analysis, the correlation pearson relationship between self  confidence to learning outcomes of students after given problem solving approach onlinear program obtained  that there is positive relationship between self confidence with learning outcomes, with correlation value is 0.691. Based on the results of the analysis, it can be concluded that there is significant relationship between self confidence with learning outcomes of  students after given problem solving approach on linear program at SMAN 1 Bonti . Keywords: Self Confidence,Learning Outcomes,Problem Solving